2020
DOI: 10.1007/s40799-019-00358-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Deformation Measurement by the Sampling Moiré Method from Video Recording and its Application to Bridge Engineering

Abstract: Measuring accurate dynamic deformation distribution for large-scale structures inexpensively and efficiently is a crucial challenge of structural health monitoring. In this study, a simple technique for measuring the deflection and vibration frequency from a captured video, based on the sampling Moiré method is developed. The striking advantage over conventional measurement using sensors and other imaging techniques are that the developed technique allows accurate measurement of two-dimensional deformations at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…For geometric feature, some scholars have proposed deflection measurement method based on sampling Moiré pattern. 32,33 Gray feature has certain requirements on the gray information of the measured target surface. The most representative technology using gray feature is the digital image correlation (DIC) technology, which has the advantages of subpixel displacement positioning and high accuracy.…”
Section: Feature Detection and Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…For geometric feature, some scholars have proposed deflection measurement method based on sampling Moiré pattern. 32,33 Gray feature has certain requirements on the gray information of the measured target surface. The most representative technology using gray feature is the digital image correlation (DIC) technology, which has the advantages of subpixel displacement positioning and high accuracy.…”
Section: Feature Detection and Matchingmentioning
confidence: 99%
“…The displacement information can be further used to evaluate the deflection. 32 Using 2D grids, the displacement of the research object can be measured in two directions simultaneously. With the help of high-speed cameras, dynamic displacement curves over time can be obtained by this method.…”
Section: Feature Detection and Matching Based On Geometric Featurementioning
confidence: 99%
“…This method uses a charge-coupled device (CCD) or complementary metal-oxide semiconductor (CMOS) sensor to capture a single image of a specimen grating of known pitch during deformation. Only one image is handled to evaluate the phase distribution by generating multiple phase-shifted moiré patterns by the thinning-out, down-sampling, and interpolation of the sequential pixels through phase analysis [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Through the phase difference of the moiré fringe prior to deformation to that of post-deformation, the displacement distribution is attained.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this has been expanded to the displacement measurement of a concrete bridge for a high-speed railway in Japan using retroreflective moiré markers. The two-dimensional (2-D) in-plane displacements at multiple locations could be easily measured from recorded digital images [11], even for the measurement of the deflection and vibration of a large-scale concrete bridge from captured video with a commercial cinema camera [12] in recent times. Further, in terms of experiments, comparative experiments conducted in a columnar cantilever beam connected to a loading jack and laser displacement meter demonstrated the effectiveness of the method for deformation measurement when the errors between the measurements were compared [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…In vibration-based SHM, the latest study by Ri et al [73] used downsized image data from a bridge-field experiment. The study demonstrated that JPEG image quality of 20% was the threshold to balance between an effective compression and the measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%